Ekonomi Politik Pengadaan Vaksin oleh Indonesia di Tengah Persaingan Politik Global [The Political Economic Perspective of Vaccine Procurement in Indonesia in the Midst of Global Political Competition] - Ignatius Ismanto (Universitas Pelita Harapan, 2021)
The spread of COVID-19 has not only becoming a national issue but also a global issue. Vaccine are viewed as important means in preventing and/or stopping the spread of COVID-19. However, vaccine availability in the midst of the battle against the global pandemic is a highly uncertain situation. There are limited number of countries that can possibly produce the vaccine, such as the United States, China, India, Russia, and England. At the same time, this global pandemic is currently ongoing in between these powerful countries. Therefore, the distribution of the vaccine, which is a rare commodity nowadays, has become their instrument of diplomacy in expanding and strengthening their global influence. This paper uses political-economy approach in examining Indonesia’s efforts in vaccine procurement. This approach means that there are some efforts in combining the political and economy dimension to explain certain phenomenon. This approach is coming from an assumption that politics and economics are the two things that cannot be separated and both are influential towards each other. In this research, international political economy approach does not only take a look at the economic dimension of vaccine procurement, but also the political dimension about this policy. The political dimension taken by Indonesia can express its response regarding global political constellation that kept on developing. Indonesia’s strategy to avoid or to be somewhat independent from a specific country is also an interesting consideration. Vaccine procurement policy by Indonesia is also becomes a reflection from the free and active political foreign policy, where Indonesia has a tendency not to be too close with another competing countries, especially the major players. Bahasa Indonesia Abstract: Penyebaran COVID-19 tidak hanya menjadi isu nasional bagi setiap negara tetapi juga telah menjadi isu global. Vaksin dipandang sebagai sarana yang penting dalam pencegahan dan atau menghentikan penyebaran COVID-19. Namun, ketersediaan vaksin dalam memerangi pandemi global itu dihadapkan pada situasi yang sangat tidak menentu. Produksi vaksin hanya memungkinkan dilakukan oleh sejumlah negara yang sangat terbatas, yaitu Amerika Serikat, China, India, Rusia dan Inggris. Penyebaran COVID-19 pada saat yang sama berlangsung di tengah persaingan pengaruh negara-negara besar itu. Distribusi vaksin, sebagai komoditi yang langka, karena itu menjadi instrumen diplomasi mereka dalam memperluas dan memperkuat pengaruh global negara-negara besar itu. Tulisan ini menggunakan pendekatan ekonomi-politik dalam mengkaji upaya yang ditempuh Indonesia dalam pengadaan vaksin. Pendekatan ekonomi politik yang dimaksudkan itu berupaya memadukan dimensi ekonomi dan dimensi politik dalam menjelaskan suatu fenomena. Pendekatan ekonomi-politik bertolak dari asumsi bahwa ekonomi dan politik merupakan dua hal yang tidak bisa dipisahkan dan saling mempengaruhi. Dalam kajian ini, pendekatan ekonomi-politik internasional tidak hanya melihat dimensi ekonomi dalam pengadaan vaksin, tetapi juga sekaligus melihat dimensi politik dari kebijakan pengadaan vaksin itu. Dimensi politik dalam pengadaan vaksin yang ditempuh Indonesia itu dapat dipandang sebagai respon terhadap konstelasi politik global yang tengah berkembang. Strategi Indonesia untuk menghindari atau tidak mengandalkan vaksin pada satu negara saja menjadi isu pertimbangan yang menarik. Kebijakan pengadaan vaksin yang ditempuh Indonesia itu sekaligus merupakan pencerminan suatu kebijakan politik luar negeri yang bebas aktif, di mana sikap Indonesia yang cenderung tidak ingin berpihak pada salah satu kekuatan besar yang tengah saling bersaing.